2015
DOI: 10.1002/jez.1903
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein influences the life‐history characteristics across generations in the African striped mouse Rhabdomys

Abstract: The level of dietary protein determines the onset of reproduction, affects offspring growth and maturation, and hence influences life-history traits and fitness. However, to date, the long-term life-history consequences of protein deficiency are not well understood. We studied the transgenerational effects of different levels of dietary protein on the life-history and level of maternal behavior of the striped mouse Rhabdomys dilectus chakae in captivity. Breeding pairs were assigned to three treatments based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 82 publications
(124 reference statements)
3
14
0
Order By: Relevance
“…Stereotypic behavior is associated with present or previous (historical) stress and is often viewed as an indicator of poor welfare (Mason, , ; Mason & Rushen, ; Mason & Veasey, ). Low protein (10% digestible protein) suppresses reproduction in striped mice (Nel et al, ), and here we showed that their activity and body mass are also reduced. Therefore, protein deficiency, through its potential effects on energy deficiency and neurological changes, negatively affects striped mice and poses a concern for their welfare in captivity.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Stereotypic behavior is associated with present or previous (historical) stress and is often viewed as an indicator of poor welfare (Mason, , ; Mason & Rushen, ; Mason & Veasey, ). Low protein (10% digestible protein) suppresses reproduction in striped mice (Nel et al, ), and here we showed that their activity and body mass are also reduced. Therefore, protein deficiency, through its potential effects on energy deficiency and neurological changes, negatively affects striped mice and poses a concern for their welfare in captivity.…”
Section: Resultssupporting
confidence: 77%
“…Secondly, protein‐restricted rats apparently utilize more energy from brown adipose tissue than non‐restricted rats, thus gaining less body mass (Donald, Pitts, & Pohl, ). Therefore, protein‐restricted individuals typically have a lower body mass compared to non‐restricted individuals (Alamy & Bengelloun, ; Almeida & De Araújo, ; Kehoe, Mallinson, Bronzino, & McCormick, ; White et al, ), as also occurred in striped mice in our study and in an earlier study (Nel et al, ). Together with reduced energy availability, a lower body mass may explain why LP striped mice showed reduced levels of activity and potentially reduced levels of stereotypic behavior.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These findings are consistent with other studies that found food availability to be the main driver of population fluctuations of rodents in semiarid environments (Brown & Ernest, ; Lima, Ernest, Brown, Belgrano, & Stenseth, ; Previtali et al., ), as well as primary consumers in general (Hunter & Price, ; Kagata & Ohgushi, ). In the case of striped mice, opportunistic breeders displaying a high degree of plasticity in reproductive timing (Nel et al., ; Raynaud & Schradin, ), the population increases following elevated food availability are likely the results of prolonged reproductive seasons with many young animals starting to breed early, potentially followed by “out‐of‐season” reproduction due to more favourable conditions.…”
Section: Discussionmentioning
confidence: 99%